Influence of guideline adherence on outcome in a randomised controlled trial on the efficacy of methotrexate with folate supplementation in rheumatoid arthritis. Issue 10 (10th September 2004) - Fransen, J; Laan, R F J M; van der Laar, M A F J; Huizinga, T W J; van Riel, P L C M
Abstract : Objective: To study the influence of rheumatologists' adherence to a methotrexate guideline on efficacy and toxicity in the treatment of rheumatoid arthritis. Methods: In a 48 week randomised controlled trial of methotrexate, comparing folates with placebo, rheumatologists were advised on methotrexate dosage using a guideline reflecting daily practice. The influence of guideline non-adherence on outcome was analysed using generalised estimating equations and survival analysis. Results: In 51% of the 411 study patients the guidelines were always followed. Non-adherence resulted in lower doses of methotrexate in 25% of cases, and higher doses in 24%. The reduction in the disease activity score was significantly greater (mean −0.4; p = 0.0085) in the adherent group than in the "low dose" group; the "high dose" group did not differ from the adherent group. Dropout caused by severe adverse events did not differ between the three groups. Conclusions: There is an indication that adherence to guidelines on methotrexate dosage may benefit patients with rheumatoid arthritis by improving disease activity without increasing toxicity. For definite proof, a randomised controlled trial comparing guideline supported dosing with usual care is needed.